Innovations in the Management of Zakat in Indonesia in Increasing Entrepreneurial Interest and Poverty Reduction - Utami, Pertiwi; Basrowi, Basrowi; Nasor, Muhammad (IJISH (International Journal of Islamic Studies and Humanities), 2021)
The purpose of this study is to propose the management of BAZNAS which could become one of the role models of digital zakat because it is quite successful in managing zakat and the use of digital technology to create the interests of the people. Literature studies are used to reveal the use of digital technology in BAZNAS and how to develop digital entrepreneurship in the future. Findings from the results of the study revealed that the BAZNAS digital zakat program can reduce poverty due to empowering mustahik through digital entrepreneurship and digital technology innovation in the form of rice atm. Other digital technology implementations are digitizing zakat payments, application-based digital information technology services for muzzaki, and blockchain (i-zakat) in managing digital zakat. For the development of digital entrepreneurship, the role of government, universities, and BAZNAS must be able to work well together. The BAZNAS Model digital zakat program can be a useful reference for global zakat managers in improving digital entrepreneurial practices and zakat distribution innovation. The implications of this research are the results of observations on the practice of using BAZNAS digital zakat technology in the management of zakat based on a theoretical basis using an Islamic economic approach.